2019
DOI: 10.1152/jn.00068.2019
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale modeling of mechanotransduction in the utricle

Abstract: We review recent progress in using numerical models to relate utricular hair bundle and otoconial membrane (OM) structure to the functional requirements imposed by natural behavior in turtles. The head movements section reviews the evolution of experimental attempts to understand vestibular system function with emphasis on turtles, including data showing that accelerations occurring during natural head movements achieve higher magnitudes and frequencies than previously assumed. The structure section reviews qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 168 publications
1
8
0
Order By: Relevance
“…The functional difference between the striolar and extrastriolar HCs may be attributed to either or combination of the following mechanisms. First, hair-bundle shape and mechanical coupling between otolith and hair bundles differ across striolar and extrastriolar regions, which is thought to tune HCs to different stimulus frequency ranges 9,23,[36][37][38][39][40][41] . Second, the MET currents per unit hair-bundle de ection may differ between HCs 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The functional difference between the striolar and extrastriolar HCs may be attributed to either or combination of the following mechanisms. First, hair-bundle shape and mechanical coupling between otolith and hair bundles differ across striolar and extrastriolar regions, which is thought to tune HCs to different stimulus frequency ranges 9,23,[36][37][38][39][40][41] . Second, the MET currents per unit hair-bundle de ection may differ between HCs 42 .…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies to date have addressed the precise architecture of vestibular hair bundles in vestibular organs and their variations, or the variation of the position of these hair bundles in a given suborgan. Several groups have shown that the hair bundles of type I hair cells are wider than those of type II hair cells, with taller stereocilia, arranged to form a steeper bundle slope ( 44 , 62 , 72 , 73 ). This architecture may translate into type I bundle responses displaying a phase advance relative to those of type II hair cells.…”
Section: Evolutionary Changes In the Inner Ear: Structure-function Co...mentioning
confidence: 99%
“…Fig. 2a; [58,69]). During constant or low-frequency linear acceleration, the otolith organs work as accelerometers, i.e., the otoconial membrane lags behind the underlying neuro-epithelium due to the inertia of the otoconia, thus, causing a relative movement between the two layers that is opposite to the direction of linear acceleration (.…”
Section: Relevant Anatomy and Physiology Of The Otolith Organsmentioning
confidence: 99%
“…The otolith (macula) organs sense linear acceleration, the utricle predominantly in the horizontal plane and the saccule predominantly in the vertical plane (Fig. 2 a; [ 58 , 69 ]). During constant or low-frequency linear acceleration, the otolith organs work as accelerometers, i.e., the otoconial membrane lags behind the underlying neuro-epithelium due to the inertia of the otoconia, thus, causing a relative movement between the two layers that is opposite to the direction of linear acceleration (Figs.…”
Section: Relevant Anatomy and Physiology Of The Otolith Organsmentioning
confidence: 99%